1996
DOI: 10.1176/ajp.153.10.1301
|View full text |Cite
|
Sign up to set email alerts
|

Serum lithium levels and psychosocial function in patients with bipolar I disorder

Abstract: For patients with bipolar I disorder, standard serum lithium levels may enhance psychosocial functioning, above and beyond the effects of relapse prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…It is known that patients with standard serum lithium levels have better psychosocial functioning than patients with low serum lithium levels. This effect is partly due to the prevention of episodes (34). In our study, the reason we did not find any relationships between serum drug levels and levels of functioning may be due to the small number of cases.…”
Section: Factors Affecting the Patients' Levels Of Functioningcontrasting
confidence: 48%
See 1 more Smart Citation
“…It is known that patients with standard serum lithium levels have better psychosocial functioning than patients with low serum lithium levels. This effect is partly due to the prevention of episodes (34). In our study, the reason we did not find any relationships between serum drug levels and levels of functioning may be due to the small number of cases.…”
Section: Factors Affecting the Patients' Levels Of Functioningcontrasting
confidence: 48%
“…It has been shown that pharmacological treatment, especially using second-generation antipsychotic drugs, has an adverse effect on cognitive functions in patients with BD (33). It has been reported that lithium treatment increases the quality of life by preventing recurrence of episodes of the disorder (34). It has been reported that second generation antipsychotic drugs used in patients with BD in remission have negative effects on psychosocial functioning (28).…”
Section: Factors Affecting the Patients' Levels Of Functioningmentioning
confidence: 99%
“…Demographic variables, such as older age [120], male sex [121, 122] and low socio-economic status [17, 18, 123], may also be considered as variables that influence the functioning of bipolar patients, although these results have yet to be sufficiently replicated. Other aspects could be environmental factors, such as social support [9, 31, 32] or life events [33].…”
Section: Resultsmentioning
confidence: 99%
“…Some drugs appear to show several advantages with respect to the probability of being employed or paid for work [36, 127, 128]. Moreover, patients receiving lithium doses that achieved therapeutic serum levels had better psychosocial functioning than those receiving doses that achieved low serum levels [123], so probably treatment adherence plays an important role for functioning.…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance therapy reduces the frequency of manic episodes and diminishes the intensity of those episodes which may occur .Typical symptoms of mania include pressure of speech, motor hyperactivity, reduced need for sleep, flight of ideas, grandiosity, elation, poor judgment, aggressiveness, and possibly hostility. When given to a patient experiencing a manic episode, lithium may produce a normalization of symptomatology within 1 to 3 weeks [6] Spermatozoa were first described by Leeuwenhoek in the 17th century but it was not until 1928 that the sperm count was found to be associated with fertility potential [7]. The mammalian sperm cell consists of a head, a midpiece and a tail.…”
Section: Introductionmentioning
confidence: 99%